2011
DOI: 10.1063/1.3566006
|View full text |Cite
|
Sign up to set email alerts
|

Modulational instability of ion-acoustic waves in plasmas with superthermal electrons

Abstract: Using the reductive perturbation technique, the modulational instability of ion- acoustic waves in a plasma containing superthermal electrons is studied. It is found that the presence of superthermal electrons significantly changes the instability domain. A Lorentzian (kappa) velocity distribution function is used to model superthermal electrons. It is shown that the presence of superthermal electrons reduces the critical frequency of the modulational instability of ion-acoustic waves. Besides, due to the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…To study the MI of DAWs, we will derive the NLSE by employing the standard multiple scale (reductive perturbation) technique . Let A be the state (column) vector ( n d , u d , ϕ ) T , describing the system's state at a given position x and instant t. We shall consider small deviations from the equilibrium state A (0) = (1, 0, 0) T by taking …”
Section: Derivation Of Nlsementioning
confidence: 99%
See 3 more Smart Citations
“…To study the MI of DAWs, we will derive the NLSE by employing the standard multiple scale (reductive perturbation) technique . Let A be the state (column) vector ( n d , u d , ϕ ) T , describing the system's state at a given position x and instant t. We shall consider small deviations from the equilibrium state A (0) = (1, 0, 0) T by taking …”
Section: Derivation Of Nlsementioning
confidence: 99%
“… A=A()0+ϵA()1+ϵ2A()2+=A()0+false∑n=1ϵnA()n, where ϵ ≪ 1 is a smallness parameter. In the standard multiple scale (reductive perturbation) technique, the stretched (slow) space and time variables are commonly used by many authors as follows: ξ=ϵxvgt,τ=ϵ2t, where v g is the group velocity in the x direction. We assume that all perturbed states depend on the fast scales via the phase θ 1 = kx − ωt only, while the slow scales enter the argument of the l th harmonic amplitude Al()n, which is allowed to vary along x , A()n=false∑l=Al()nξτeilkxωitalict. …”
Section: Derivation Of Nlsementioning
confidence: 99%
See 2 more Smart Citations
“…We have employed the standard multiple-scale perturbation technique to derive the NLS equation. It was shown that in earlier investigations [30] that MI of ion acoustic waves is significantly influenced by the presence of superthermal electrons and growth rate is larger in the presence of more superthermal electrons. We have, however, investigated the combined effects of the external magnetic field, dust concentration and the superthermality of electrons on the MI of DIA wave packets.…”
Section: Introductionmentioning
confidence: 99%